Development and current status of counselling psychology in Taiwan. Issue 2 (2nd April 2016) - Tu, Su-Fen; Jin, Shuh-Ren
Abstract : This article details the three stages of counselling psychology's development in Taiwan, including pre-legislation, legislation and post-legislation. In pre-legislation stage, a brief historical review of the growth of counselling and guidance is introduced, which is the root of the contemporary counselling psychology. The process of the Psychology Act's legislation is described in legislation stage and the relationships between counselling teachers and clinical psychologist are also discussed. In the post-legislation stage, the licensure system, training programmes, main professional organizations, work settings, and the major opportunities and challenges for the counselling psychology field are presented. In addition, the article refers to data from a national survey of 124 counselling psychologists to provide a profile of the counselling psychologists in Taiwan.